Prácticas de lectura y escritura en cinco asignaturas de diferentes programas de la Universidad Sergio Arboleda (2010)
This paper presents the results of an investigation into the practices of reading and writing present in five courses of different programs assigned at the Sergio Arboleda University (Bogotá). The research derives from the following questions: What is the role of reading and writing process in the course of some programs at the University? How is assign; directed and accompanied the task of reading and writing? and how are assessed the progress and results in the process of reading and writing? The information was obtained from written tests; surveys; classroom observations and interviews with teachers of these programs. After the analysis process; were set up five units of information; which in the case of reading were reading assignment; intervention guidance; intervention to clarify; evaluation and assessments of teachers; and for the case of writing: defining text types; intervention process; intervention in the correction process; evaluation and assessments of teachers